Studies on tinapayan-an indigenous fosh ferment in Central Mindanao - Guerra, Melanie Relayson (Iloilo College of Fisheries, University of the Philippines, 1992)
Tinapayan is a Maguindanaoan carbohydrate base or Lactic Acid (LA) fish ferment prepared by fermenting anaerobcally dried fillets of murrel (pangos) with a mixture of prefermented cooked rice, spices, small amount of salt and water. The product undergoes three stages of manufacture : production f tapai (Stage 1), tapai a umay (Stage 2), and tinapayan (Stage 3). Three studies were undertaken, namely, establishment of of flavor profiles of good quality market samples of tapai a umay and tinapayan ; quantitative determination of microbial flora (by group) and physico-chemical changes in all stages of manufacture ; and determination of the effect of additional 2.5 and 5.0 % w/w salt on the quality of tinapayan. Tapai (ground rice, 50% water v/w, 2.0% w/w red pepper, and 0.01% w/w 2-week old commercial tapai) ; tapai a umay (cooked nn glutinous rice and 1.5% w/w tapai) ; and tinapayan (24 hour old tapai a umay, 2.5% w/w salt, 18.0% w/w langkuas (Curcuma zedoaria Berg., Rosc,), 0.18% lemon grass (Cymbopogon citratus), 1.5% water w/w and, dried murrel (Ophicephalus striatus) were produced in the laboratory following the native process. Tapai a umay resembled Southeast Asian saccharified rice, having a flavor blend of sweet, slightly sour and slightly alcoholic notes. Cooked tinapayan exhibited a chorizo like aroma and a flavor blend closely similar to beef tapa. Three groups of microroganism, that is, molds, yeast and LABs which are believed to originate from the commercial starter were found growing in association in all three stages of tinapayan manufacture. Stage I was governed by molds and yeasts, the LABs proliferated only between 12-48 hours when the moisture was 40-50 %. The dried starter (9.49% moisture) contained log 9 cfu/g each of molds and yeasts, and log 3 cfu/g of LABs. In Stage 2, the growth of LABs were favored, the molds and yeasts showed decreasing growth trends. The 24-hour old tapai a umay contain about log 6 cfu/g each of molds and yeasts, and log 5 cfu/g of LABs. The pH dropped to about 4.0 after 6 hours, % Titrable Acid (% TA, expressed as Lactic Acid) ranged from 0.10 to 0.30% and moisture, content increased to 67%.In Stage 3, the molds and yeasts maintained theri population at log 6 cfu/g. the LABs reached log 7 cfu/g onday 9. The pH of the system ranged from about 5.0 to 6.0, % TA had its peak at 1.0% and the product has an average and salt content of 4.86% after the 15th day of fermentation. The addition of 5% salt (about 7.0% in the final product) in P3 sample resulted to a reduction in the number of yeasts to log 5 cfu/g and LABs to log 5 cfu/g, and an increase in the number of molds to log 6 cfu/g. The pH of the system was low rangig from 5.5-6.5 with a correspondingly low amount of % TA (0.51%) average). The odor, flavor and general acceptability of the cooked product was comparatively inferior than that of market sample. The fish ferments with final salt contents of about 5.0% or less, taht is, with additional 2.5% w/w salt and with no additional salt had better sensory and acceptability scores than the P3 sample. Both products attained the characteristic odor and flavor scores similar to the market sample in less than 15 days of fermentation. The general acceptability scores were also good.
Thesis (M. S. Fisheries) - University of the Philippines in the Visayas, September 1992.
Keywords: Tinapayan